Workplace incivility and organisational identification: The role of affective organisational commitment and perceived insider status. Issue 5 (3rd September 2019) - Guo, Ju; Qiu, Yanjun
Abstract : We investigated the mediating role of affective organisational commitment (AC) and the moderating role of perceived insider status (PIS) on the relationship between workplace incivility (WINC) and organisational identification (OID). A total of 417 employees from 66 private Chinese universities participated in the study (females = 267; academic staff = 64.1%). They completed items adapted from existing measures of AC, PIS, WINC, and OID. We applied Baron and Kenny's hierarchical regression analysis method to test for the mediating effect of AC on the relationship between WINC and OID. In addition we utilised Hayes' bootstrapping method to test for the moderation effect of PIS on the relationship between WINC and OID. Results from these analysis indicated AC mediated the relationship between WINC and OID so that the direct effect of WINC on OID became insignificant while PIS weakened the indirect relationship between WINC and OID through AC. Findings are consistent with the view that WINC has a negative impact on employee quality of organisational citizenship.